REPRESENTATION OF NATIONALISM VALUES IN FAOZAN RIZAL’S HABIBIE & AINUN MOVIE SCRIPT - Sirait, Elisa; Ekalestari, Susi (JOURNAL OF LANGUAGE, 2025)
This research explores the nationalism values shown in the movie Habibie & Ainun, directed by Faozan Rizal. The story focuses on the life of Indonesia's third president, B.J. Habibie, and his wife, Ainun. The film also portrays nationalism through civic, romantic, and economic lenses. Using a qualitative method with content analysis, the research found various types of nationalism values in the movie, such as civic nationalism, romantic nationalism, cultural nationalism, and economic nationalism. These values are reflected in Habibie's dedication to building the nation, establishing Indonesia’s airplane industry, and his deep love for his country. The research also identifies the purposes of nationalism in the movie, such as building national pride, unity, and a sense of responsibility to the country. This research demonstrates that movies can be powerful tools for promoting national values, particularly among the younger generation. This study contributes to film and cultural studies by revealing how cinematic narratives can construct national identity